A Study on the Anatomical Relationship of the Lumbar Extrapedicular Puncture Approach with the Spinal Nerve and its Branches. Issue 11 (1st June 2021) - Zhong, Yuan; Luo, Lei; Zhao, Chen; Li, Pei; Dong, Bozan; Wang, Zili; Jiang, Dianming; Zhou, Qiang; Liu, Liehua
Abstract : Mini: The anatomical relationship of the extrapedicular approach with the spinal nerve and its branches was researched in cadavers. Three types of extrapedicular paths were simulated: puncture inside the medial branch (MB), puncture outside the MB, and puncture outside the lateral branch (LB). At L1–L3, puncture outside the LB could avoid damage to these nerves. Study Design: An anatomical study in 15 cadavers. Objective: To observe the anatomical relationship of the extrapedicular puncture approach with the spinal nerve and its branches, evaluate the risk of injury to these nerves and recommend a safe puncture path for lumbar extrapedicular percutaneous vertebroplasty (PVP) and percutaneous kyphoplasty (PKP). Summary of Background Data: There have been no reports on the anatomical relationship of the extrapedicular approach with the spinal nerve and its branches. Methods: The positions, diameters, and paths of the anterior ramus (AR), medial branch (MB), and lateral branch (LB) outside the pedicles of L1–L4 were observed, and the related anatomical parameters were measured. Three types of extrapedicular puncture paths were simulated: puncture inside the MB, puncture outside the MB, and puncture outside the LB. By evaluating the risk of injury to the MB, LB, and AR, an appropriate puncture path was recommended. Results: During puncture inside the MB, the incidence of MB injury was 93.3% to 100%. During puncture outside the MB, the incidence rates of MB injury at L1 and L2 were 10.0% and 3.3%, respectively, and the incidence of LB injury at L4 was 10.0%. During puncture outside the LB, there were no cases of injury to the LB or MB. There was no incidence of AR injury during L1–L3 extrapedicular puncture, but the risk of AR injury was 3.3% when the procedure was performed at L4. The recommended technique is puncture outside the LB, where the needle vertically crosses the transverse process, slides inward, and advances while being held tightly against the bone. Conclusion: Extrapedicular puncture occurs adjacent to the spinal nerve and its branches, posing a risk of injury to these nerves. At the L1–L3 levels, puncture outside the LB can avoid damage to the spinal nerve and its branches. Level of Evidence: N/A.